Comparison of C2 dome-like laminectomy with C2 partial laminectomy for upper cervical ossification of the posterior longitudinal ligament - Miao, Dazhuang; Gao, Xianda; Zhen, Zihao; Yang, Dalong; Wang, Hui; Ding, Wenyuan (Frontiers in Surgery, 2023)
Objective: To compare surgical outcomes of C2 dome-like laminectomy with C2 partial laminectomy in patients with ossification of the posterior longitudinal ligament (OPLL) up to the C2 level and above. Methods: There were 32 patients who underwent surgical treatment for OPLL up to C2 divided into: C2 dome-like laminectomy group (C2-DOM group, n=16) and C2 partial laminectomy group (C2-PL group, n=16). The cervical curvature (CCI), dura width at C2/3, Japanese orthopedic association (JOA) score, recovery rate (RR), neck disability index (NDI) score, and visual analogue scale (VAS) score were evaluated and compared preoperatively and during the follow‑up period. Results: At the last follow-up, the JOA, NDI and dura width at C2/3 significantly improved in the two groups, in which the improvement of NDI score in the C2-DOM group was significantly greater than that in the C2-PL group, the dura width at C2/3 in the C2-PL group was significantly larger than that in the C2-DOM group, and there was no significant difference in JOA score between the two groups. The VAS scores in both groups were higher than those before surgery. The VAS score more increased in the C2-PL group than that in the C2-DM group. The CCI in both groups decreased compared with before surgery, and there was no significant difference in CCI between the two groups. Conclusion: C2 dome-like laminectomy has less damage, and it does not enhance the patient’s postoperative axial symptoms. C2 partial laminectomy can achieve more adequate decompression without increasing the risk of postoperative cervical kyphosis.